Physical and mental health impact of COVID-19 on children, adolescents, and their families: The Collaborative Outcomes study on Health and Functioning during Infection Times - Children and Adolescents (COH-FIT-C&A) - Luo, Wen; Cai, Qian; Zhou, You; Cai, Yepeng; Song, Huizi; Zhang, Yiran; Chen, Yuying; Liao, Yuexia (figshare, 2022)
Additional file 1.